Dual Tumor Suppressor and Tumor Promoter Action of Sirtuins in Determining Malignant Phenotype - Carafa, Vincenzo; Altucci, Lucia; Nebbioso, Angela (Frontiers in Pharmacology, 2019)
Sirtuins, class III histone deacetylases, are differentially expressed in several human cancers, where they display both oncogenic and tumor-suppressive properties depending on cellular context and experimental conditions. Sirtuins are involved in many important biological processes and play a critical role in cancer initiation, promotion and progression. A growing body of evidence indicates the involvement of sirtuins in regulating three important tumor processes: epithelial-to-mesenchymal transition (EMT), invasion and metastasis. Many sirtuins are responsible for cellular metabolic reprogramming and drug resistance by inactivating cell death pathways and promoting uncontrolled proliferation. In this review, we summarize current knowledge on the role of sirtuins in cancer and discuss their puzzling dual function as tumor suppressors and tumor promoters, important for the future development of novel tailored sirtuin-based cancer therapies.